ANALISI YURIDIS TERHADAP PENGECUALIAN PEMBAKARAN LAHAN DAN HUTAN BERDASARKAN PASAL 69 AYAT (2) UNDANG-UNDANG NOMOR 32 TAHUN 2009 TENTANG PENGLOLAAN DAN PERLINDUNGAN LINGKUNGAN HIDUP - Gaol, Hendra Eriant Dikser Lumban; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Indonesia is a country rich in natural wealth. Among them are forests. According to Big Indonesian Dictionary, the forest is a land overgrown with trees and usually not maintained by people. Some types of forest in Indonesia according to climate is tropical rain forest, forest season, savanna, steppe and mangrove forest (mangrove). The type of forest based on its function is conservation forest, protection forest and production forest.Forest fires are frequent in Indonesia, especially on the islands of Sumatra and Kalimantan. In history it is said that forest fires have occurred in Indonesia since the 18th century. Starting from a fire in the forest area between the Kalanan River and Cempaka (now Sampit River and Katingan River) Central Kalimantan Province in 1877. Based on the above explanation, the author of this law provides a knowledge of a thing that should be raised into a study with Title